Wavevector and Frequency Multiplexing Performed by a Spin‐Decoupled Multichannel Metasurface. Issue 1 (1st December 2019) - Xu, He‐Xiu; Hu, Guangwei; Jiang, Menghua; Tang, Shiwei; Wang, Yanzhao; Wang, Chaohui; Huang, Yongjun; Ling, Xiaohui; Liu, Haiwen; Zhou, Jiafeng
Abstract: Achieving kaleidoscopic wavefront controls with a thin flat plate is pivotal for increasing data capacity yet still challenging in integrated optics. An anisotropic metasurface provides an efficient recipe primarily for linear polarization, but is less efficient for multiple functionalities at arbitrary spin states. Here, a strategy of realizing a spin‐decoupled high‐capacity multifunctional metasurface by multiplexing the frequency and wavevector degree of freedom (DoF) is reported. By integrating both geometric and dynamic phases in split ring resonators and crossbars in a chessboard configuration, the inherent limitation of spin‐flipped Pancharatnam–Berry phases can be completely decoupled between two spin states. Such released extraordinary DoF unprecedentedly increases the capability to yield kaleidoscopic wavefront control. To verify the significance, two proof‐of‐concept metadevices that are nearly impossible in conventional metasurfaces are experimentally demonstrated with four‐port wavefront manipulations, exhibiting spin‐, frequency‐, and wavevector‐dependent anomalous reflections, lensing, orbital angular momentum generation, and wavevector‐multiplexed vortex scattering, along with two‐dimensional holograms. Both numerical and experimental results illustrate quad‐distinct functionalities with up to ten channel beams and ≈93% efficiency, because of the completely suppressed crosstalk among different operation modes, angular wavevectors, and spins. The finding in triple‐DoF multiplexing is expected to generate great interest in electromagnetic integration with emerging DoFs. Abstract : A spin‐decoupled high‐capacity multifunctional metasurface is proposed by multiplexing the frequency and wavevector degree of freedom. By integrating both geometric and dynamic phases in a split ring resonator and crossbars in a chessboard super meta‐atoms, the inherent limitation of spin‐flipped Pancharatnam–Berry profiles can be completely decoupled between two spin states. Two proof‐of‐concept metadevices are experimentally demonstrated with the four‐port wavefront manipulations.